2018
DOI: 10.4236/aasoci.2018.82008
|View full text |Cite
|
Sign up to set email alerts
|

Silence in Intercultural Collaboration: A Sino-Dutch Research Centre

Abstract: China is widely recognized as a significant scientific partner for Western universities. Given that many Western universities are now operating in the Chinese context, this study investigates the everyday conversations in which international partnerships are collaboratively developed and implemented. In particular, it draws attention to the interpretations of the meanings attached to silence in these conversations, and how these can have unintended consequences for how these joint partnerships are accomplished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The study found an important negative correlation between team-member exchange and silence behavior, while workplace loneliness and silence behavior showed a positive relationship, as did psychological capital and silence behavior. Verouden et al (2018) also confirmed the silence of Chinese interlocutors. The researchers faced difficulty in obtaining information from them during their experiments.…”
Section: Silence Inter-culturally and Cross-culturallysupporting
confidence: 60%
“…The study found an important negative correlation between team-member exchange and silence behavior, while workplace loneliness and silence behavior showed a positive relationship, as did psychological capital and silence behavior. Verouden et al (2018) also confirmed the silence of Chinese interlocutors. The researchers faced difficulty in obtaining information from them during their experiments.…”
Section: Silence Inter-culturally and Cross-culturallysupporting
confidence: 60%
“…Over the past couple of decades, the research discourse on silence has engaged in the quest for a more profound understanding of silence. Recent contributions to research-based knowledge include the consideration of misperceived silence in communication [43,44] , the reinterpretation of silent behaviour in multicultural contexts [45,46] , the dynamics of frustration with silence in intercultural communication [47][48][49] , the process of negotiating multiple identities [50] , the range of meanings decoded in silent experiences [23,51,52] , and the modifiability of behaviour [53][54][55] .…”
Section: Social Views On Silencementioning
confidence: 99%
“…Paying attention to silence in qualitative research has been presented as a need and a growing trend, particularly in the scientific domain (Mellor and Webster 2017) and in the context of different communication interactions (Verouden et al 2018). The analysis of silence's social and affective functions is necessarily more interpretative than the study of the cognitive or pragmatic functions.…”
Section: Introductionmentioning
confidence: 99%